Long-term changes of ichthyoplankton communities in an Iberian estuary are driven by varying hydrodynamic conditions. (1st December 2020) - Monteiro, M; Azeiteiro, U M; Martinho, F; Pardal, M A; Primo, A L
Abstract: Ichthyoplankton assemblages are key components of estuaries worldwide, playing a vital role as nurseries for fish larvae. Nonetheless, estuaries can be highly affected by ongoing climate change. Impacts of climate variability on ichthyoplankton assemblages will have consequences for marine pelagic food webs and fish populations biology, namely recruitment. This study aims to investigate the influence of environmental variability on an interannual abundance of ichthyoplankton assemblages of the Mondego estuary (Portugal). For this, an ichthyoplankton sampling programme of 13 years (2003–2015) along six distinct sampling stations was analysed to evaluate spatial, seasonal and interannual changes of ichthyoplankton distribution over periods of wet, regular and dry conditions. The ichthyoplanktonic community was dominated by Pomatoschistus spp. across all seasons and conditions, with higher larval abundances during summer and spring. Main changes were related to species seasonality and phenology as well as an increase in the number of marine species during extreme events. The larval fish community showed a strong relationship with the regional and local environment over the study, presenting a distinct yet highly variable structure during the 2009–2013 period. Reported changes will likely trigger major changes in species dominance and abundance, with clear ecological and socio-economic implications.